THE EFFECT OF SERVICE QUALITY AND PROMOTIONAL PRICES ON CUSTOMER SATISFACTION AT PT SWAKARSA JAYA INDONESIA - Silverius Laia; Bahdin Nur Tanjung; Irvan Muhrizal; Nuzuliati (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This research is motivated by the importance of customer satisfaction in facing increasingly competitive service business competition, especially at PT Swakarsa Jaya Indonesia which still faces various complaints related to service quality and the effectiveness of promotional prices. This study aims to analyze the effect of service quality and promotional prices on customer satisfaction at PT Swakarsa Jaya Indonesia. The research method used is a quantitative descriptive approach with data collection techniques through questionnaires using a Likert scale. The study population amounted to 1,000 consumers with a sample of 91 respondents determined using the Slovin formula. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results showed that service quality has a positive and significant effect on customer satisfaction with a calculated t value of 5.810 > t table 1.986 and a significance value of 0.000 < 0.05. Promotional prices also have a positive and significant effect on customer satisfaction with a calculated t value of 2.519 > t table 1.986 and a significance value of 0.000 < 0.05. Simultaneously, service quality and promotional prices significantly influence customer satisfaction. Research findings indicate that improving service quality supported by appropriate promotional pricing strategies can increase customer satisfaction levels. An Adjusted R Square value of 90% indicates that variations in customer satisfaction can be explained by service quality and promotional prices, while the remaining 10% is influenced by other factors outside the study. Thus, service quality and promotional prices are important factors in increasing customer satisfaction at PT Swakarsa Jaya Indonesia.